2016
DOI: 10.1177/0020764016631368
|View full text |Cite
|
Sign up to set email alerts
|

Do people with bipolar disorders have access to psychosocial treatments? A survey in Italy

Abstract: Few people with bipolar disorders had access to psychosocial treatments. Even in a well-developed system of community care, offer of psychosocial interventions for bipolar disorders is inadequate. This issue should be a target for future research on dissemination and implementation strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…In Italy, issues of accessibility are also present. For example, rates of patients with bipolar disorder receiving structured psychosocial treatments in Italy range from 0.7% for couple/family therapy to 6.1% for individual psychotherapy (Barbato et al ., 2016 ). Although Italy has a public healthcare system, only about 3% of healthcare funds are allocated toward mental health (Caporale, 2023 ).…”
Section: Models Of Practice and Training In Clinical Psychologymentioning
confidence: 99%
“…In Italy, issues of accessibility are also present. For example, rates of patients with bipolar disorder receiving structured psychosocial treatments in Italy range from 0.7% for couple/family therapy to 6.1% for individual psychotherapy (Barbato et al ., 2016 ). Although Italy has a public healthcare system, only about 3% of healthcare funds are allocated toward mental health (Caporale, 2023 ).…”
Section: Models Of Practice and Training In Clinical Psychologymentioning
confidence: 99%
“…Neither residency programmes for psychiatrists nor university training for clinical psychologists has changed significantly over the years, and this has a marked impact on the quality of mental health care, as shown by several studies published in the last four decades (Volpe et al ., 2014 ). In addition, several surveys found that psychosocial treatments, including formal psychotherapies, are not widely available and are underused for the treatment of patients who may be in need of them (Barbato et al ., 2016 ).…”
Section: Mental Health Care and Psychotherapy In Italymentioning
confidence: 99%
“…In this study, none of the programme facilitators had any previous experiences in delivering a Positive Psychology intervention but achieved to do so with the supervision of experienced clinicians. A benefit of this intervention programme is that it could be easily taught to mental health professionals and be delivered under supervision of an experienced psychotherapist, which addresses the global shortage of experienced therapists and appropriately organised services (Barbato, Vallarino, Rapisarda, Lora, Miguel, & de Almeida, 2016).…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%